2019
DOI: 10.3390/jmse7040107
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Image Processing Module for Autonomous Underwater Vehicles through Integration of Visual Recognition with Stereoscopic Image Reconstruction

Abstract: This study investigated the development of visual recognition and stereoscopic imaging technology, applying them to the construction of an image processing system for autonomous underwater vehicles (AUVs). For the proposed visual recognition technology, a Hough transform was combined with an optical flow algorithm to detect the linear features and movement speeds of dynamic images; the proposed stereoscopic imaging technique employed a Harris corner detector to estimate the distance of the target. A physical A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Traditional marine target detection methods often combine color segmentation [ 11 , 12 ], texture feature analysis [ 13 ], and shape feature analysis [ 14 ]. However, these methods are sensitive to external factors, resulting in poor detection performance in complex marine environments.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional marine target detection methods often combine color segmentation [ 11 , 12 ], texture feature analysis [ 13 ], and shape feature analysis [ 14 ]. However, these methods are sensitive to external factors, resulting in poor detection performance in complex marine environments.…”
Section: Introductionmentioning
confidence: 99%
“…This set of modules includes many different types of tools and skids, such as rotary disk cutters, wire and cable cutters, pipeline camera skids, manipulator skids, water-jetting tooling skids, and rotatory brush skids. The significance of using automated alerting systems is highlighted by this diversity [3].…”
Section: Introductionmentioning
confidence: 99%
“…They are extensively utilized for both scientific reasons like ocean exploration and industrial ones like internal and external inspections of underwater pipelines and the structural assessment of offshore structures. Recently, a number of ROV applications for ocean research have been reported [1]- [4]. Based on the application, they range in their size from a micro or mini ROV which is used to reach areas at shallow depths to a work class ROV which is used for ocean floor exploration and inspection at unreachable depths.…”
Section: Introductionmentioning
confidence: 99%